Rethinking the Empty Ballot Box in Pilkada: Between Democratic Substance and Legal Formalism - Sultoni Fikri; Syofyan Hadi; Baharuddin Riqiey; Rizky Bangun Wibisono (Universitas Negeri Surabaya, 2025)
The phenomenon of single-candidate elections in regional head elections (Pilkada) poses challenges to the democratic principles of directness, generality, freedom, confidentiality, honesty, and fairness. To address such electoral impasses, the